2017
DOI: 10.1001/jamacardio.2016.5224
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation, Type 2 Diabetes, and Non–Vitamin K Antagonist Oral Anticoagulants

Abstract: We highlight the increased thromboembolic risk with coexisting AF and type 2 diabetes. We recommend that further studies be done to evaluate the potential benefits of anticoagulation for all patients who have both and the potential for non-vitamin K oral anticoagulants to have greater benefits than risks over vitamin K antagonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 68 publications
3
38
0
3
Order By: Relevance
“…The prevalence of both atrial fibrillation and type 2 diabetes has been rising rapidly [2,3]. Studies have shown that when both conditions coexist, the risk for thromboembolism is increased [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of both atrial fibrillation and type 2 diabetes has been rising rapidly [2,3]. Studies have shown that when both conditions coexist, the risk for thromboembolism is increased [4].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, diabetes is one of the factors included in the risk stratification scheme CHA 2 DS 2 -VAS c -score used to identify high-risk patients with atrial fibrillation that may benefit from anticoagulation treatment in order to prevent stroke from thromboembolism [11]. However, guidelines are inadequate regarding recommendations for anticoagulation when both conditions coexist [4]. Hence, increased understanding is needed on how the risk of atrial fibrillation interacts with type 2 diabetes and coexisting diabetes-specific risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Efficacy analyses were based on the intention‐to‐treat population. A study‐level meta‐analysis of the four trials has shown that the use of non‐vitamin K oral anticoagulants vs warfarin significantly reduced the composite efficacy endpoint both in participants with diabetes and in those without diabetes, with no significant interaction by diabetes status and treatment ( P value for interaction 0.72; Table ) . Moreover, as participants with diabetes were at increased absolute risk for the primary endpoint compared with those without diabetes, similar relative risk reduction across the diabetes mellitus population using non‐vitamin K oral anticoagulants translated into greater absolute benefit .…”
Section: Efficacy Of Non‐vitamin K Oral Anticoagulants In Participantmentioning
confidence: 99%
“…Atrial fibrillation and diabetes mellitus are both major causes of morbidity and mortality, with a prevalence and severity that rise with age . For reasons not completely elucidated and after adjustment for confounders , diabetes mellitus and atrial fibrillation often co‐exist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation